Dilemmas in caring for older adults in Zhejiang Province, China: a qualitative study - Sha Ma; Jianwei Shi; Lu Li (BMC, 2019)
Abstract Background Owing to the increase in life expectancy and sickliness, caring for older adults has become a major challenge in China, where the traditional care system is disintegrating and community- and home-based care have been introduced to respond to this 'silver wave'. However, there is limited knowledge of the dilemmas associated with caring for older adults and the acceptability of community- and home-based care for this population. Methods Participants were recruited from Xihu District, Hangzhou, from June to July 2017. In-depth interviews were conducted using semi-structured questionnaires. Audio recording, verbatim transcription, and thematic analysis were conducted. Results A total of 64 older adults from four communities were interviewed. Half of the participants had multiple chronic diseases. The very old individuals and those with severe diseases and in poor financial conditions were observed to be struggling the most. Health status, financial capability, and personality were the main factors affecting the care process. Participants cited the following reasons for staying away from nursing homes: misunderstanding, negative environment, a sense of shame, loneliness, and financial limitations. Community- and home-based cares are popular forms of old-age care; however, some participants exhibited a lack of knowledge about such services. Conclusion A multi-layered old-age care system is urgently needed for older adults in Zhejiang Province. Further, it is important that such a system integrates the care provided through community- and home-based services with that offered by nursing homes. Community- and home-based care for older adults needs to be prioritised, and the quality of care provided in nursing homes should be improved.